EFFECT OF INFLATION, ER, SBI AND NET INCOME ON INDUSTRIAL AND CHEMICAL SECTOR COMPANIES - Rantika Sitanggang; Nina Purnasari; Santy Angelina Hutabalian; Mikhael Bachchanta Sembiring (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
IHSG is a stock price index number that has been compiled and calculated by generating a trend, where the index number is a number that is processed in such a way that it can be used to compare events that can be changes in stock prices from time to time. The purpose of this study was to determine whether there is a significant effect between inflation, exchange rates, SBI interest rates, and net income on the composite stock price index. There are 80 company populations during 2017-2019 with a total sample of 34. This type of research uses explanatory research, the research location is carried out on the IDX. Data collection was obtained from BEI, BPS and BI. The data analysis technique used statistical analysis techniques with multiple linear regression analysis methods. Based on the tests that have been carried out, the results show that inflation, interest rates, and net income have no effect on the IHSG, but the exchange rate has a significant effect on the IHSG